¿Nos encontramos frente a una nueva clase de mutagenos? - Cuyubamba, Oscar R. (1990)
1,3-Dinitronaphthalene, previous1y identified in particulate organic matter, easily forms covalent adducts with DNA nucleotides at room temperature. The mutagenic potency of a related dinitropolycyclic aromatic hydrocarbon (dinitroPAH) with meta disubstitution, namely 1,3-dinitrofluoranthene, is rather independent of the Salmonella Typhimurium tester strain (TA98, TA98NR and TA98/l, 8DNP6) when assayed according to the Ames Test. This unusual behavior suggests that it does not require metabolic activation via the "classical nitroreductase" and/or the acetylase. The fact that 1,3--dinitronaphthalene readily forms covalent adducts with DNA nucleotides further suggests that dinitroPAH with meta nitro-groups may not require the usual metabolic activation pathways.